ANTIOXIDANT ACTIVITIES OF STEM, LEAVES, AND FRUITS EXTRACTS OF PEPINO (SOLANUM MURICATUM AITON) WITH DPPH AND CUPRAC METHODS - Alysia Febiana, Nethania
Free radicals are highly reactive compounds that can cause cellular damage to DNA, proteins, and lipids, leading to chronic diseases such as cancer. Antioxidants are stable compounds that can protect body cells from free radical species by donating their electrons, allowing them to bond with free radical compounds. Pepino (Solanum muricatum Aiton) is rich in vitamin C, which is known to have antioxidant properties. This study was conducted to determine the antioxidant activity of extracts from pepino stems, leaves, and fruits using the DPPH and CUPRAC methods, to determine the correlation between the two antioxidant activity tests, to determine the total phenolic and flavonoid content, to determine the quantitative correlation between the total phenolic and flavonoid content and the antioxidant activity values of the DPPH and CUPRAC methods, and to identify and determine flavonoid compounds level in the selected extract. Extraction was performed using the reflux method, using n-hexane, ethyl acetate, and ethanol solvents. Antioxidant activity was determined using DPPH and CUPRAC, and the total phenolic and flavonoid content was determined using UV-visible spectrophotometry. Identification and determination of flavonoid compound in the selected extract were performed using high-performance liquid chromatography (HPLC). The antioxidant activity of pepino DPPH ranged from 1.625-39.269 mg AEAC/g, while the CUPRAC antioxidant activity ranged from 2.336-54.488 mg AEAC/g. The highest total phenolic content was obtained from the ethyl acetate extract of pepino stems (18.493±1.080 g GAE/100 g). The highest total flavonoid content was obtained from the hexane extract of pepino leaves (9.541±0.636 g QE/100 g). Phenolic and flavonoid compounds in stems, leaves, and fruits extracts showed significant positive correlation and contributed greatly to the DPPH and CUPRAC antioxidant activities, except for the hexane leaves extract in CUPRAC antioxidant activity. Overall, the results of the DPPH and CUPRAC antioxidant activities were linear. Ethyl acetate extract of pepino fruits contained kaempferol at concentration of 0.112%.